2022
DOI: 10.3390/su14148652
|View full text |Cite
|
Sign up to set email alerts
|

Digital Finance, Environmental Regulation, and Green Technology Innovation: An Empirical Study of 278 Cities in China

Abstract: Digital finance provides a premises guarantee for green technology innovation, and effective environmental regulation helps to achieve green and sustainable development. This article selects Chinese urban panel data from 2011 to 2019 to explore the impact mechanism of the influence of digital finance and environmental regulation on the innovation capacity of green science and technology. It is found that extensive financing channels and the strong information-matching ability of digital finance have a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…This paper also found that the effects of FER and IER showed significant regional differences and that the effects of FER and IER decreased from the eastern region to the central and western regions. Similarly, Zhang et al [ 58 ] and Hu et al [ 59 ] showed that there is regional heterogeneity in the effect of environmental regulation on GTI. Shao et al [ 60 ] showed that environmental regulation has a positive effect on GTI in eastern China but not in the central and western regions.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 96%
“…This paper also found that the effects of FER and IER showed significant regional differences and that the effects of FER and IER decreased from the eastern region to the central and western regions. Similarly, Zhang et al [ 58 ] and Hu et al [ 59 ] showed that there is regional heterogeneity in the effect of environmental regulation on GTI. Shao et al [ 60 ] showed that environmental regulation has a positive effect on GTI in eastern China but not in the central and western regions.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 96%
“…Secondly, the application of the QCA method is limited to cross-section data, primarily focusing on consistency and neglecting coverage exploration. Although the impact of environmental regulation policies on green technology innovation and green total factor productivity has been extensively studied [ [45] , [46] , [47] ], few scholars have examined the mechanism through which carbon trading policies affect green technology innovation. Furthermore, there is a lack of research exploring the impact of carbon trading policies on the “quantity” and “quality” of green technology innovation from a micro perspective, considering the time and space effects.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it effectively curbs pollution investment, which not only helps to accelerate the green transformation of China’s economy, but also helps to promote technological progress in environmental protection, new energy, and energy conservation. In addition, digital finance can play the role of lubricant, accelerate the free circulation and effective allocation of capital, information, digital, technology, and other elements, and correct the market failure and financial fragmentation caused by information asymmetry in traditional finance [ 42 , 43 , 44 ]. It is an important hand to realize green development, transformation, and upgrading, and plays a decisive role in supporting green industry and sustainable economic and social development.…”
Section: Theoretical Analyses and Research Hypothesesmentioning
confidence: 99%